ESTIMASI KANDUNGAN BAHAN ORGANIK TANAH DI LAHAN TANAMAN JERUK, KECAMATAN DAU, KABUPATEN MALANG MENGGUNAKAN INDEKS VEGETASI DAN SISTEM INFORMASI GEOGRAFIS - Saputra, Muhammad Fiqriansyah Wiradirga; Munir, Mochammad (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Citrus plants (Citrus sp.) are most plants that grow in Petungsewu Village, Dau District. The decreased productivity of citrus plants causes the availability of citrus plants also to decrease. This needs to be increased to meet citrus plants' needs. The influence of soil organic matter is the main factor causing a decrease in the productivity of citrus plants in Petungsewu Village, Dau District. Therefore, it is necessary to estimate soil organic matter using the NDVI vegetation density index to obtain adequate and efficient results. Reliability testing was also carried out to know the accuracy level of the estimates made. The research was conducted at the Citrus Plantation and Subtropical Fruit Research Institute in Petungsewu Village, Dau District, Malang Regency. Estimation of soil organic matter using the NDVI vegetation density index showed an accuracy rate of 81.1%. The results of the accuracy analysis were strengthened by the presence of a paired t-test with a value of t = 0.01 and a value of p = 0.991.